Високоефективна багатоканальна система контролю параметрів телевізійних та радіомовних передавачів - Грицик, В.В.; Кравець, І.І.; Лозинський, О.М.; Опотяк, Ю.В.; Пінкевич, Ю.П. (Видавничий дім "Академперіодика" НАН України, 2008)
The modern state of radio engineering meters and measuring systems made by CIS countries for the control over TV and broadcast transmitter parameters is analyzed. The lacks of the existent systems are indicated. New approaches and a highly effective multichannel measuring system for broadcast transmitters based on these approaches and developed by the authors are described. The perspective ways of development and improvement of the system are indicated.